2022
DOI: 10.1093/nar/gkac076
|View full text |Cite
|
Sign up to set email alerts
|

GCAT|Panel, a comprehensive structural variant haplotype map of the Iberian population from high-coverage whole-genome sequencing

Abstract: The combined analysis of haplotype panels with phenotype clinical cohorts is a common approach to explore the genetic architecture of human diseases. However, genetic studies are mainly based on single nucleotide variants (SNVs) and small insertions and deletions (indels). Here, we contribute to fill this gap by generating a dense haplotype map focused on the identification, characterization, and phasing of structural variants (SVs). By integrating multiple variant identification methods and Logistic Regressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 74 publications
(111 reference statements)
1
10
0
Order By: Relevance
“…We thus centered our testing on the accuracy of different parameters on SV calling. In fact, some recent approaches specifically developed for human genomes [22,30] may outcompete perSVade in human samples. However, such methods rely on previously defined sets of known SVs, which are not available in most taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus centered our testing on the accuracy of different parameters on SV calling. In fact, some recent approaches specifically developed for human genomes [22,30] may outcompete perSVade in human samples. However, such methods rely on previously defined sets of known SVs, which are not available in most taxa.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the role of SVs remains largely unexplored across eukaryotes.Inferring SVs from short reads is challenging because it relies mostly on indirect evidence coming from de novo assembly alignment, changes in read depth, or the presence of discordantly paired / split reads in read mapping analysis [16][17][18][19][20][21]. Long-read-based SV calling may avoid some of these limitations, but short read-based SV calling remains a cost-effective strategy to find SVs in large cohorts [14,15,22]. Recent benchmarking studies compared the performance of different tools in human genomes and found that SV calling accuracy is highly dependent on the methods and filtering strategy used [15,…”
mentioning
confidence: 99%
“…Genotyping was done using the Infinium Expanded Multi-Ethnic Genotyping Array (MEGAEX) (ILLUMINA, San Diego, California, USA). Then, we imputed both SNVs and SVs, with IMPUTE2, and using GCAT|Panel as reference [40], an ancestry-geographically matched panel generated by whole-genome sequencing. The final core set included a total of 10,216,971 variants with MAF ≥ 0.01 and INFO score ≥ 0.7 (21,620 SVs,and 10,195,351 SNVs and small indels).…”
Section: Genetic Variantsmentioning
confidence: 99%
“…Standard genome-wide threshold (p < 5e-8) was kept for significance. SNPs were functionally annotated and mapped to the closest gene with SnpEff [40]. Manhattan and quantile-quantile (QQ) plots were generated to explore the results, as well as a 3D Manhattan representation that provides a visual representation of the common GWAS hits between the different traits.…”
Section: Genome-wide Association Analysis Of Phototypementioning
confidence: 99%
See 1 more Smart Citation